WOMEN IN MEMES: Reactualization of the Hadith “Prohibiting Women from Traveling without a Mahram” on Social Media - Miski, Miski; Istiqomah, Nurul (UIN Sunan Kudus, 2024)
This paper explains the trends and implications of understanding religious texts through hadith memes prohibiting women from traveling without a mahram. Using a discourse-genealogical approach, a qualitative type of study and descriptive, semiotic and intertextual analysis models, this study shows that the relevance of hadith existence in memes goes hand in hand with efforts to reactualize the Prophet's message. Hadith memes are positioned as a shari'ah as well as psychological control over the audience to carry out the message of the hadith in the contemporary context. Moreover, the mediatization of the hadith shows one main tendency: strengthening translationistic logic in the discourse of understanding religious texts. Furthermore, this understanding is also trapped in patriarchal logic, which automatically triggers the appearence of more complex criticism and debate from experts.